Some New Common Fixed Point Theorems under Strict Contractive Conditions in G-Metric Spaces. (13th September 2012) - Mustafa, Zead
Abstract : We introduce some new types of pairs of mappings( f, g ) on G -metric space called G -weakly commuting of type (A f ) and G - R -weakly commuting of type (A f ). We obtain also several common fixed point results for these mappings under certain contractive condition in G -metric space. Also some examples illustrated to support our results, and comparison between different types of pairs of mappings are studied.